The conceptual flaws of the new EU development agenda from a political economy perspective, or why change is problematic for a donor-driven development policy - Simon Hartmann (Austrian Foundation for Development Research (ÖFSE), 2012)
The European Union (EU) recently presented a new development policy agenda that centers on the subject of change. We first assess the approach of the EU policy by discussing change in the sense of how it is used within the EU agenda. Second, we relate it to two recently published political economy frameworks (North et al. 2009, and Acemoglu/Robinson 2012), which discuss the mechanisms of political and economic changes within societies, as well as their subsequent problems. Consideration of critiques of their works and alternative approaches (for example, Reinert 2007, Rodrik 2011a, Chang 2011a) provides deeper insights into the mechanisms of change and answers some open questions. From there, we discuss their implications for foreign aid approaches, then use the findings to uncover some conceptual flaws in the EU Agenda for Change. Finally, we extract five guiding recommendations for development policy makers in the EU.
Keywords: 330; Entwicklungshilfe; Wirkungsanalyse; EU-Staaten